Dilated Cardiomyopathy in a Young Patient With an FLNC Gene Mutation - Alex David Sotomayor-Julio; Andrea Facio-Lince García; Wikler Bernal-Torres; Sebastián Seni-Molina; Juan David López-Ponce de León (Case Reports in Medicine)
Discussion: This case highlights the importance of investigating genetic causes in young patients presenting with unexplained dilated cardiomyopathy. Although truncating FLNC mutations are rare, they are associated with adverse outcomes, including major ventricular arrhythmias and sudden cardiac death. Atypical biventricular involvement suggests overlapping phenotypes, complicating the diagnostic process. Advanced imaging modalities, comprehensive management strategies, and early genetic testing are crucial to optimizing patient outcomes.